Inhibition of cell proliferation by the somatostatin analogue RC-160 is mediated by somatostatin receptor subtypes SSTR2 and SSTR5 through different mechanisms. - Buscail, L (1995)
Effects of the stable somatostatin analogue RC-160 on cell proliferation, tyrosine phosphatase activity, and intracellular calcium concentration were investigated in CHO cells expressing the five somatostatin receptor subtypes SSTR1 to -5. Binding experiments were performed on crude membranes by using [125I-labeled Tyr11] somatostatin-14; RC-160 exhibited moderate-to-high affinities for SSTR2, -3, and -5 (IC50, 0.17, 0.1 and 21 nM, respectively) and low affinity for SSTR1 and -4 (IC50, 200 and 620 nM, respectively). Cell proliferation was induced in CHO cells by 10% (vol/vol) fetal calf serum, 1 microM insulin, or 0.1 microM cholecystokinin (CCK)-8; RC-160 inhibited serum-induced proliferation of CHO cells expressing SSTR2 and SSTR5 (EC50, 53 and 150 pM, respectively) but had no effect on growth of cells expressing SSTR1, -3, or -4. In SSTR2-expressing cells, orthovanadate suppressed the growth inhibitory effect of RC-160. This analogue inhibited insulin-induced proliferation and rapidly stimulated the activity of a tyrosine phosphatase in only this cellular clone. This latter effect was observed at doses of RC-160 (EC50, 4.6 pM) similar to those required to inhibit growth (EC50, 53 pM) and binding to the receptor (IC50, 170 pM), implicating tyrosine phosphatase as a transducer of the growth inhibition signal in SSTR2-expressing cells. In SSTR5-expressing cells, the phosphatase pathway was not involved in the inhibitory effect of RC-160 on cell growth, since this action was not influenced by tyrosine and serine/threonine phosphatase inhibitors. In addition, in SSTR5-expressing cells, RC-160 inhibited CCK-stimulated intracellular calcium mobilization at doses (EC50, 0.35 nM) similar to those necessary to inhibit somatostatin-14 binding (IC50, 21 nM) and CCK-induced cell proliferation (EC50, 1.1 nM). This suggests that the inositol phospholipid/calcium pathway could be involved in the antiproliferative effect of RC-160 mediated by SSTR5 in these cells. RC-160 had no effect on the basal or carbachol-stimulated calcium concentration in cells expressing SSTR1 to -4. Thus, we conclude that SSTR2 and SSTR5 bind RC-160 with high affinity and mediate the RC-160-induced inhibition of cell growth by distinct mechanisms.